Mulheres em luta: uma outra história do Movimento "Queixadas" de Perus - Alves, Maria Madalena Ferreira (2011)
This dissertation, Women in struggle: another point of view about Perus Queixadas‟ Movement , is the result of a research about the Cement Factory workers strike which has happened in Perus whereabouts in Sao Paulo suburbs. The aim of this work was to show the women participation in this movement. The women mentioned in this work are not workers neither feminists, they are wives, they are housewives that experienced their husbands seven years strike consequences. They were required to take the family responsibility and, at the same time, to participate in pickets and in another events in the workers movement favor, in many cases. One can say that the struggle kept going on through ecological claims in defending environment (against the air pollution caused by the factory cement thrown in air) when the strike was over. The objective is to provide visibility to these ladies act and to contribute with a different point of view about women which goes beyond the common-sense normally given to them a fragile being that hides their organization and struggle capability that was unveiled when their families were threatened. The research has been conducted using different traditional data gathering tools: interviews, focus group, historical documents and testimonials